Model Pendidikan Islam Multikultural - Hasbullah; Nurhasanah (Ikatan Da'i Indonesia, 2024)
Multicultural Islamic education model is an effort to answer the challenges of education today. With the model, Islamic education will be present not only as a subject matter but also as a role model for sustainable development and a tool for conducting research as a whole in Indonesia as a plural nation with cultural diversity. This research uses a library research approach. The research data were collected through library data, including textbooks, articles, papers, and other sources. Multicultural Islamic Education views that education must be based on Theological, Philosophical, Juridical, Sociological, and Psychological foundations. The multicultural education model will foster high awareness of tolerance and acceptance on the cultural differences and equality of human rights.